Ginkgetin delays the progression of osteoarthritis by inhibiting the NF-κB and MAPK signaling pathways - Liang Zhu; Yanchi Bi; Ting Liang; Po Zhang; Xiao Xiao; Tengbo Yu (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA) is considered an advancing chronic degenerative joint disease, leading to severe physical functional impairment of patients. Its development is closely related to increased inflammation and oxidative stress within the joint. Ginkgetin (GK), a natural non-toxic chemical, has proven anti-inflammatory, antioxidant, anti-tumor, and neuroprotective effects. Methods First, this study utilizes network pharmacology to explore the intrinsic connection between GK and OA. In vitro, SW1353 human cartilage cells were stimulated with Tert-butyl hydrogen peroxide (TBHP), and different GK concentrations were pre-treated to evaluate its protective effects. GK's anti-inflammatory and antioxidative effects were comprehensively assessed via MTT assay, western blot, cell immunofluorescence, ELISA, and transcriptome sequencing. Potential underlying mechanisms were also explored. In vivo, OA was induced in rats via anterior cruciate ligament transection (ACLT), and GK's impact on cartilage protection was further assessed via histological analysis and western blot. Results Network pharmacology has revealed that GK regulates OA via several key pathways, especially NF-κB, HIF-1, PI3K-AKT, and substances like reactive oxygen species. In vitro experiments showed GK effectively reverses oxidative stress damage from TBHP, inhibits inflammatory factor release, and protects Extracellular matrix (ECM) from degradation. These functions may be achieved via the NF-κB and MAPK signaling pathways. In vivo experiments showed GK significantly reduced proteoglycan loss from ACLT and inhibited matrix metalloproteinase 13 (MMP13) and ADAMTS5 (A disintegrin and metalloproteinase with thrombospondin motifs 5) production, effectively preventing cartilage degeneration in rats. Conclusion These findings suggest that GK has potential as a therapeutic agent for OA, offering new strategies and directions for OA treatment.